CBIA-DIARRHEA FOR IMPROVING KNOWLEDGE, ATTITUDE AND BEHAVIOR OF MOTHER IN INFANT DIARRHEA TREATMENT FOR BINA KELUARGA BAHAGIA (BKB) BANGUNTAPAN, BANTUL - Ajeng Padma Kumala; Sri Suryawati (Faculty of Pharmacy, Universitas Gadjah Mada, 2016)
Diarrhea in infants becomes emerged issue in Indonesia (MOH, 2010). The role of mother as a 'key person' is expected to have a level of knowledges, attitudes, and behaviors that qualified for the treatment of diarrhea. CBIA shown to improve knowledge, attitudes and maternal behavior in choosing a drug (Suryawati, 1995). CBIA-Diarrhea adopted from CBIA is expected to gain the knowledge, attitudes, and behavior of the mother in the management of diarrhea so as to reduce morbidity and infant mortality. For improving knowledge, attitudes, and behavior of the mother in the prevention of diarrhea in infants with CBIA-Diarrhea method and to develop methods from CBIA into CBIA-Diarrhea. This type of research is quasi-experimental design with pre-test to post-test control group design. There are 40 respondents to the treatment group and 40 respondents to the control group. Selected respondents has entered inclusion criteria, and selected randomly. CBIA-Diarrhea intervention and readings of diarrhea in infants by the experimental group, and in the control group performed conventional lectures with material non-diarrhea. relationship between variables was analyzed by Wilcoxon and Man-Whiteney with a confidence level of 95 %. There are a significant difference between pre and post intervention of CBIA which developed a new module CBIA-Diarrhea. The knowledge, attitudes and maternal behavior increased after intervention by the method of CBIA-Diarrhea. The development of CBIA to CBIA-Diarrhea shown to improve knowledge, attitudes and maternal behavior for the treatment ofdiarrhea in infants.